ROLE OF WOMEN IN PANCHAYATI RAJ IN HARYANA - Komal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women have always been an important integral part of the society, culture, economy, politics etc. aspects of any country. However, with time, the presence and contribution (role) of women in these systems has been increasing and decreasing. If world history is studied in the context of the status of women, it is known that women had an independent existence since the primitive age, but with time this independence turned into dependence. For example, women played an active role during the French Revolution (1789 AD). But the French Constitution of 1791 AD gave women the status of passive citizens, which finally ended in 1946 with French women getting the right to vote. If the political role of women is studied in the context of Indian history, then perhaps the decline of women’s participation in public activities started after the Rigvedic era. But in the modern era, women re-entered politics during the First World War. In the present study, the role of women in Panchayati Raj in Haryana has been described. Apart from this, while evaluating the presence of women Sarpanch and Panch in the districts of Haryana, how can women be made aware of their position and powers? This has also been suggested.